Ergonomic Exercise-Based Nursing Care for Addressing Community Health Deficits in Rural Areas - Kamila, Nurul; Istifada, Rizkiyani; Rasni, Hanny; Mustapa, Gesit Wira (Al-Hijrah Indonesia, 2025)
Uncontrolled hypertension due to a lifestyle that lacks healthy physical activity caused complications in the form of a stroke. The study aimed to describe the effect of ergonomic exercise in community nursing care on the blood pressure in rural areas. The research design uses a case study of a community with hypertension. There are 34 respondents in the aggregate of adults and older people. Data analysis uses nursing care with the Indonesian Nursing Diagnosis, Outcome, and Interventions Standard. Thirty-two respondents showed a significant decrease in systolic blood pressure (p-value <0.001), and 16 respondents indicated a substantial reduction in diastolic blood pressure (p-value 0.005). Thirty-three respondents experienced increased scores from pre-test to post-test (p-value <0.001). Public health development interventions can improve community health status through ergonomic exercise. Ergonomic exercise provides complementary benefits in managing hypertension among adults and older people by decreasing blood pressure and minimizing stroke risk.